The Effect of Potential Rush Money and Fraud on the Need for External Audit in Rural Credit Institutions with Leadership Idealism as a Moderating Variable - Putu Candra Ardiana Putra; Gede Adi Yuniarta; I Putu Gede Diatmika (Universitas Pendidikan Ganesha, 2023)
This study aims to examine the effect of potential rush money and fraud on the need for external audit in Rural Credit Institutions (LPD) with leadership idealism as a moderating variable. This study used the head of the LPD in Bali Province who is still actively operating as a population. The method of determining the sample used is the purposive sampling method. Data analysis used SEM-PLS (Structural Equation Modeling-Partial Least Square) Version 3. The result shows that the potential for rush money has a positive effect on the need for external audit services for Rural Credit Institutions, which indicates that the potential for rush money that is likely to be experienced is capable of increasing the need for external audit services. The result shows that the potential for fraud has a positive effect on the need for an external audit of the Rural Credit Institution, which indicates a potential for fraud that may be experienced can increase the need for external audit services. The results show that the idealism of the leadership can strengthen the influence of the potential rush of money on the need for an external audit of Rural Credit Institutions and the idealism of the leadership can increase the influence of potential fraud on the need for external audit services for Rural Credit Institutions. Therefore, rural credit institutions need to pay attention to the importance of conducting regular external audits to ensure that their business practices are running well and in accordance with established standards.